Increased ABCC4 Expression Induced by ERRα Leads to Docetaxel Resistance via Efflux of Docetaxel in Prostate Cancer - Huang, Houbao; Li, Jing; Shen, Jing; Lin, Ling; Wu, Xu; Xiang, Shixin; Li, Yawei; Xu, Yujie; Zhao, Qijie; Zhao, Yueshui; Kaboli, Parham Jabbarzadeh; Li, Mingxing; et al. (Frontiers in Oncology, 2020)
Docetaxel is a major treatment for advanced prostate cancer (PCa); however, its resistance compromises clinical effectiveness. Estrogen receptor-related receptor alpha (ERRα) belongs to an orphan nuclear receptor superfamily and was recently found to be closely involved in cancer. In the present study, we found that ERRα was involved in docetaxel resistance in PCa. Overexpression of ERRα conferred docetaxel resistance in PCa cell lines, and cells with ERRα downregulation were more sensitive to docetaxel. Among the drug resistance-related genes, ABCC4 demonstrated synchronous expression after ERRα manipulation in cells. Moreover, both ERRα and ABCC4 were overexpressed in the docetaxel-resistant cell, which could be reversed by ERRα knockdown. The knockdown of ERRα also reversed the reduced drug accumulation in the docetaxel-resistant cell. We also demonstrated for the first time that ABCC4 was a direct target of ERRα as determined by the CHIP and luciferase assays. Bioinformatics analysis revealed high expression of ERRα and ABCC4 in PCa patients, and a number of potential ERRα/ABCC4 targets were predicted. In conclusion, our study demonstrated a critical role for ERRα in docetaxel resistance by directly targeting ABCC4 and stressed the importance of ERRα as a potential therapeutic target for drug-resistant PCa.